To the sources! On historical source criticism in metal studies: Concert flyers, album covers, and band T-shirts - Pichler, Peter (Popular Music History, 2023)
Metal studies is usually considered to be a fundamentally interdisciplinary field of research. However, the disciplines that were included at its beginning (mostly sociology, cultural anthropology, musicology, and philosophy) are still theoretically dominant. As a consequence, several important research questions that do not reflect these disciplines’ epistemologies have remained unanswered to this day. To a great extent, this applies to historical research questions on metal scenes. In this respect, the author argues that metal studies could benefit from the expertise of history in general and source criticism in particular. In order to develop this argument, necessary basic traits of contemporary historical source criticism are introduced. Then, the author proceeds by individually discussing three fundamental types of sources that are structurally tied to the historical long-term processes in metal scenes: concert flyers, album covers and band T-shirts. Research into the Styrian metal scene in south-eastern Austria provides examples. To conclude, it is posited that starting from a semiotic concept of source criticism and then adapting such a concept for the specific purposes of metal studies is necessary to nurture historical awareness and the accuracy of relevant research.